Monte Carlo simulations of the dose from imaging with GE eXplore 120 micro‐CT using gate. Issue 10 (9th September 2015) - Bretin, Florian; Bahri, Mohamed Ali; Luxen, André; Phillips, Christophe; Plenevaux, Alain; Seret, Alain
Abstract : Purpose: Small animals are increasingly used as translational models in preclinical imaging studies involving microCT, during which the subjects can be exposed to large amounts of radiation. While the radiation levels are generally sublethal, studies have shown that low‐level radiation can change physiological parameters in mice. In order to rule out any influence of radiation on the outcome of such experiments, or resulting deterministic effects in the subjects, the levels of radiation involved need to be addressed. The aim of this study was to investigate the radiation dose delivered by the GE eXplore 120 microCT non‐invasively using Monte Carlo simulations ingate and to compare results to previously obtained experimental values. Methods: Tungsten X‐ray spectra were simulated at 70, 80, and 97 kVp using an analytical tool and their half‐value layers were simulated for spectra validation against experimentally measured values of the physical X‐ray tube. A Monte Carlo model of the microCT system was set up and four protocols that are regularly applied to live animal scanning were implemented. The computed tomography dose index (CTDI) inside a PMMA phantom was derived and multiple field of view acquisitions were simulated using the PMMA phantom, a representative mouse and rat. Results: Simulated half‐value layers agreed with experimentally obtained results within a 7% error window. The CTDI ranged from 20 to 56 mGy and closely matched experimental values. Derived organ doses in mice reached 459 mGy in bones and up to 200 mGy in soft tissue organs using the highest energy protocol. Dose levels in rats were lower due to the increased mass of the animal compared to mice. The uncertainty of all dose simulations was below 14%. Conclusions: Monte Carlo simulations proved a valuable tool to investigate the 3D dose distribution in animals from microCT. Small animals, especially mice (due to their small volume), receive large amounts of radiation from the GE eXplore 120 microCT, which might alter physiological parameters in a longitudinal study setup.